2004
DOI: 10.1210/en.2003-0946
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Phenotypic Array of Hypothalamic Neuronal Cell Models to Study Complex Neuroendocrine Disorders

Abstract: Knowledge of how the brain achieves its diverse central control of basic physiology is severely limited by the virtual absence of appropriate cell models. Isolation of clonal populations of unique peptidergic neurons from the hypothalamus will facilitate these studies. Herein we describe the mass immortalization of mouse primary hypothalamic cells in monolayer culture, resulting in the generation of a vast representation of hypothalamic cell types. Subcloning of the heterogeneous cell populations resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
182
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(189 citation statements)
references
References 21 publications
6
182
0
1
Order By: Relevance
“…These cell lines have been thoroughly characterized, show neurosecretory properties, express neuron specific markers and have classical neuronal morphology. 17,19 In this study, we show that 17b-estradiol (E 2 ) directly decreases NPY secretion in both the mHypoE-42 and mHypoA-2/12 neurons. Using pharmacological estrogen receptor (ER)-a and (ER)-b receptor specific agonists/antagonists, we were able to determine that the E 2 -mediated decrease occurred through ER-a in both of the hypothalamic cell lines.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…These cell lines have been thoroughly characterized, show neurosecretory properties, express neuron specific markers and have classical neuronal morphology. 17,19 In this study, we show that 17b-estradiol (E 2 ) directly decreases NPY secretion in both the mHypoE-42 and mHypoA-2/12 neurons. Using pharmacological estrogen receptor (ER)-a and (ER)-b receptor specific agonists/antagonists, we were able to determine that the E 2 -mediated decrease occurred through ER-a in both of the hypothalamic cell lines.…”
Section: Introductionmentioning
confidence: 60%
“…To examine the mechanisms by which E 2 regulates NPY within an individual NPY-expressing neuron, we used hypothalamic neuronal cell models derived from both embryonic (e17) and adult (2 month-old) primary cell culture, the mHypoE-42 17 and mHypoA-2/12, 18 respectively. These cell lines have been thoroughly characterized, show neurosecretory properties, express neuron specific markers and have classical neuronal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Having confirmed that the physical properties of the CD vector were suitable for siRNA delivery, in vitro testing was carried out in a mouse embryonic hypothalamic neuronal cell line, mHypoE N41, 36 and in primary rat embryonic (E18) hippocampal neurons. )) and zeta potential (charge (mV)) of CD-siRNA complexes at increasing mass ratios (MR; μg CD/μg siRNA) were measured in DIW (final siRNA concentration 3 μg/mL) using dynamic light scattering (Malvern ZetaSizer Nano).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Belsham et al have managed to develop cell lines that are representative of the enormous range of hypothalamic cell types [2,14]. N39, developed from primary mouse fetal hypothalamic cultures, is one such homologous neuronal cell line.…”
Section: Introductionmentioning
confidence: 99%
“…N39, developed from primary mouse fetal hypothalamic cultures, is one such homologous neuronal cell line. As they express both CRF 1 and CRF 2 receptors and Ob-R [2,32] these hypothalamic N39 cells have been used to further understand endogenous receptor signal transduction, the possible function of leptin, and the regulation of CRF and Ucns by leptin in the hypothalamus. Cui et al used these cells to demonstrate that leptin signaling involves the JAK-STAT3 pathway [13].…”
Section: Introductionmentioning
confidence: 99%